Psychological effects of retirement on elite athletes - Marthinus, J. M. (University Stellenbosch, 2007)
This study was designed to gain a better understanding of the way in which the quality of the sport-career termination is quantitatively affected by athletic and non-athletic factors. A further objective of this study was to contribute and broaden the knowledge base on the athletic career termination process and endeavour to add new information to the existent body of knowledge on the career-ending process in the world of sport. This study is a sport-specific view on South African track and field and road running athletes` retrospective views on their retirement. In line with the relevant literature, the influence of athletic (voluntariness and gradualness of sport-career termination, subjective view of athletic achievements, postsport life planning, and athletic identity) and non-athletic factors (e.g., age, educational status) on different aspects of sport-career difficulties was investigated. In phase 1 of the research, 104 retired track and field athletes completed an adapted version of the Cecic-Erpic`s (2000) Sports Career Termination Questionnaire II (SCTQ II). These athletes had been retired for no less than one year with an athletic career at national and international level and were asked to describe in retrospect their experiences and reactions to their athletic career termination. The SCTQII was developed to evaluate the characteristics of the sport-career termination process, the characteristics of the active sport-career termination transition to post-sport life, and adaptation to post-sport life. In phase 2 of the study, 23 retired South African elite athletes were individually interviewed. An interview guide was developed which probed the sport career of the athletes in depth, from the initial start to the sport career to the process of disengaging from elite sport. The data from the interviews were content analysed.